Hubungan Tingkat Pengetahuan dan Kepatuhan Konsumsi Tablet Tambah Darah Pada Remaja Putri Dengan Status Anemia - Erlinda Riska Putri; Rosmauli Jerimia Fitriani (SEHATI: Jurnal Kesehatan, 2024)
Anemia is one of the nutritional problems in Indonesia. The prevalence of anemia among adolescents in Indonesia is 32 percent. The purpose of this study is to analyze the relationship between the level of knowledge and compliance of the consumption of blood supplement tablets in teenage daughters with anemia status in the State High School 1 Bantul. Type of analytical research with cross-sectional design. Sampling using purposive sampling with a total of 87 pupils. Data collection using knowledge level questionnaires and compliance consumption of blood supplement tablets. The results showed that 73.6% of girls had a good level of knowledge, 60.9% of girls did not obey taking blood supplements, but only 3.4% had anemia. Analysis of data using fisher's exact test with the results there was no significant relationship between knowledge level and anemia status with a value of p= 1,00 (p more than 0,05), there is no significant relation between consistency of blood supplement tablet consumption with anemia state with a score of p = 1,00, (p more than 0,05). The conclusion of this study was no relationship between the level of knowledge and anemic status, nor was there a relationship between compliance of tablet supplement intake with a status of anemia.